Industrial Discourse in Voluntary Environmental Disclosure Questionnaires Responses: A Case Study. (July 2021) - Lane, Christina
Deploying a grounded theory approach, this case study examines 9 years of a nonrenewable energy company's responses to a voluntary environmental disclosure questionnaire to discover how industrial discourse about climate change is used by industry writers. Through using the rhetorical strategies of emotions, affect, and mythic narrative within theory, balancing norm, and dominion frames, the company communicates climate change does not impact their secure economic future due to their proactive approach toward regulatory compliance with technological innovation and attentive internal and external policy oversight.